Modeling the Driving Factors of Educational Technology Innovation in Indonesian Universities: A Hybrid ISM–ANP Approach - Satria Abadi; Mad Helmi ab Majid; Y. Yohakim Marwanta; Didi Susianto (International Journal of Artificial Intelligence Research, 2025)
This study aims to model the critical enablers driving technological innovation in higher education institutions in Indonesia by integrating Interpretive Structural Modeling (ISM) and Analytic Network Process (ANP). The hybrid approach provides both structural and quantitative insights into the interrelationships among eight identified enablers: policies and regulations, digital infrastructure, faculty competence, technology incentives, industry collaboration, student literacy, innovation culture, and data security. The ISM results classify policies and regulations and digital infrastructure as driving factors that form the foundational layer of innovation ecosystems. Meanwhile, faculty competence, technology incentives, and industry collaboration serve as linkage factors that bridge strategic policies and operational implementation, whereas student literacy, innovation culture, and data security emerge as dependent factors representing the system’s outcomes. The ANP results reinforce the ISM structure, revealing that policies and regulations (0.215) and digital infrastructure (0.187) have the highest influence, followed by faculty competence (0.142) and industry collaboration (0.130). The combined ISM–ANP framework demonstrates that sustainable educational technology innovation requires a synergistic interaction between governance, human resources, and digital culture. The findings provide a comprehensive model that can guide universities and policymakers in formulating evidence-based digital transformation strategies within the Indonesian higher education context